Categorization, Fast and Slow - Starko, Vasyl (East European Journal of Psycholinguistics, 2017)
The title of this study is inspired by Daniel Kahneman’s best-selling book Thinking, Fast and Slow. In it, the Nobel Prize winner explains in great detail the working of two systems of human reasoning: System 1, which is fast, automatic, associative, subconscious, involuntary and (nearly) effortless, and System 2, which is slow, intentional, logical, conscious, effortful and requires executive control, attention, and concentration. This distinction applies to human categorization as well. Each of the two labels refers, in fact, to a set of systems, which is why the designations Type 1 and Type 2 processes are preferable. The default-interventionist architecture presupposes the constant automatic activation of categories by Type 1 processes and interventions of Type 2 processes if necessary. Type 1 categorization relies on the ‘shallow’ linguistic representation of the world, while Type 2 uses ‘deep’ extralinguistic knowledge. A series of linguistic examples are analyzed to illustrate the differences between Type 1 and Type 2 categorization. A conclusion is drawn about the need to take this distinction into account in psycholinguistic and linguistic research on categorization. References Barrett, F., Tugade, M. M., & Engle, R. (2004). Individual differences in working memory capacity in dual-process theories of the mind. Psychological Bulletin, 130(4), 553–573. Chaiken, S., & Trope, Y. (Eds.). (1999). Dual-process theories in social psychology. New York, NY: Guilford Press. Devine, P. G. (1989). Stereotypes and prejudice: Their automatic and controlled components. Journal of Personality and Social Psychology, 56, 5–18. Evans, J. St. B. T., & Stanovich, K. (2013) Dual-process theories of higher cognition: Advancing the debate. Perspectives on Psychological Science, 8(3), 223–241. Geeraerts, D. (1993). Vagueness’s puzzles, polysemy’s vagaries. Cognitive Linguistics, 4(3), 223–272. Heider, Eleanor Rosch (1973). On the internal structure of perceptual and semantic categories. In: Cognitive Development and the Acquisition of Language, (pp. 111–144). T. E. Moore, (ed.). New York: Academic Press Kahneman, D. (2003). A perspective on judgement and choice. American Psychologist, 58, 697–720. Kahneman, D. (2015). Thinking, Fast and Slow. New York: Farrar, Straus and Giroux. Kahneman, D., & Frederick, S. (2002). Representativeness revisited: Attribute substitution in intuitive judgement. In: Heuristics and Biases: The Psychology of Intuitive Judgment, (pp. 49–81). T. Gilovich, D. Griffin, & D. Kahneman, (eds.). Cambridge, MA: Cambridge University Press. Lakoff, G. (1973). Hedges: A study in meaning criteria and the logic of fuzzy concepts. Journal of Philosophical Logic, 2, 458–508. Lakoff, G. (1987). Women, Fire, and Dangerous Things. Chicago, London: University of Chicago Press. Reber, A. S. (1993). Implicit Learning and Tacit Knowledge. Oxford, England: Oxford University Press. Stanovich, K. E. (1999). Who is Rational? Studies of Individual Differences in Reasoning. Mahwah, NJ: Erlbaum. Stanovich, K. E., & West, R F. (2000). Individual difference in reasoning: implications for the rationality debate? Behavioural and Brain Sciences, 23, 645–726. Старко В. Категоризаційні кваліфікатори// Проблеми зіставної семантики. 2013, № 11. С. 132–138. Starko, V. (2013). Katehoryzatsiini kvalifikatory. Problemy Zistavnoyi Semantyky, 11, 132–138. Sun, R., Slusarz, P., & Terry, C. (2005). The interaction of the explicit and the implicit in skill learning: A dual-process approach. Psychological Review, 112, 159–192. Teasdale, J. D. (1999). Multi-level theories of cognition–emotion relations. In: Handbook of Cognition and Emotion, (pp. 665–681). T. Dalgleish & M. J. Power, (eds.). Chichester, England: Wiley. Wason, P. C., & Evans, J. St. B. T. (1975). Dual processes in reasoning? Cognition, 3, 141–154. Whorf, B. L. (1956). The relation of habitual thought and behavior to language. In: Language, Thought, and Reality. Selected Writings of Benjamin Lee Whorf, (pp. 134– 159). Cambridge, Massachusetts: The M.I.T. Press. (originally published in 1941) Wierzbicka, A. (1996). Semantic Primes and Universals. Oxford: Oxford University Press.